2011
DOI: 10.1007/s12149-011-0478-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcome prediction and disease extension by quantitative 2-deoxy-2-[18F] fluoro-d-glucose with positron emission tomography in patients with small cell lung cancer

Abstract: FDG-PET imaging is a valuable tool in the management of patients with SCLC for a more accurate staging. The use of quantitative PET parameters may have a role in prediction of stage and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 18 publications
2
33
0
1
Order By: Relevance
“…If a 50% threshold is implemented, the use of TLG rather than volume may be justified on the basis of a significant variability difference. This suggestion is supported by literature data on patients with small cell lung cancer and non-small cell lung cancer (4,7). For all thresholds, the fact that both TLG and volume variability were greater than SUVmean variability (Fig.…”
Section: Discussion Tlg Variabilitysupporting
confidence: 85%
“…If a 50% threshold is implemented, the use of TLG rather than volume may be justified on the basis of a significant variability difference. This suggestion is supported by literature data on patients with small cell lung cancer and non-small cell lung cancer (4,7). For all thresholds, the fact that both TLG and volume variability were greater than SUVmean variability (Fig.…”
Section: Discussion Tlg Variabilitysupporting
confidence: 85%
“…Arslan et al [16] found that total lesion glycolysis (SUV max > 50%) was the only quantitative PET parameter that could predict survival in patients with SCLC (p = 0.027).…”
Section: Discussionmentioning
confidence: 99%
“…Diğer bir çalışmada, konvansiyonel evreleme yöntemleri ile sınırlı hastalık tespit edilen hastalarda FDG-PET/BT eklenerek yeniden yapılan evrelemede hastaların %8,3-9,5'da yaygın hastalık evresinde olduğu görülmüştür (72,73). Arslan ve ark FDG-PET/BT ve BT ile yapılan evrelemenin doğruluğu-nu ve genel sağ kalım ile ilişkisini değerlendirmişlerdir (74). BT ile yapılan evreleme ile karşılaştırıldığında 25 hastanın 9'unda evrenin yükseldiği (%36) ve 2 hastada ise evrenin azaldığı (%8) bulunmuştur.…”
Section: Küçük Hücreli̇ Akci̇ğer Kanseri̇ (Khak) Evrelemeunclassified